2016
DOI: 10.1080/00015458.2016.1242214
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, management and survival outcomes of primary cutaneous melanoma: a ten-year overview

Abstract: Patients generally presented with thin melanomas. Lymph node disease and distant metastases remained infrequently observed during following years, and general 1- and 5-year overall disease-specific survival rates exceeded 85%. Small numbers of rescue surgery and palliative medical treatment warrant further centralisation and investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Further functional and mechanistic characterization demonstrated that SLNCR1 increases melanoma invasion by transcriptionally upregulating matrix metalloproteinase 9 (MMP9) in cooperation with the brain‐specific homeobox protein 3a (Brn3a) and the androgen receptor (AR) . This study may partially why males have higher incidence of melanoma metastases and exhibit an overall lower survival …”
Section: Deregulated Lncrnas In Melanomamentioning
confidence: 96%
“…Further functional and mechanistic characterization demonstrated that SLNCR1 increases melanoma invasion by transcriptionally upregulating matrix metalloproteinase 9 (MMP9) in cooperation with the brain‐specific homeobox protein 3a (Brn3a) and the androgen receptor (AR) . This study may partially why males have higher incidence of melanoma metastases and exhibit an overall lower survival …”
Section: Deregulated Lncrnas In Melanomamentioning
confidence: 96%
“…Cutaneous melanoma is a very aggressive cancer whose incidence has rapidly increased worldwide. The prognosis is generally poor given the propensity of melanoma cells to spread to distant sites while evading immune system control [ 1 ]. The relevant events that favour the immune escape of melanoma cells include the variable antigenic profile of the tumor cells, the enrolment of suppressor cells, the release of soluble factors within the microenvironment and the propagation of signals driven by melanoma microRNAs (miRNAs) [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with a local primary melanoma, metastasis is an important prognostic factor. For primary melanomas, histopathological staging is usually a prognostic indicator (de Giorgi et al, ; Hayes et al, ; Tsao et al, ; Aubuchon et al, ; Hwang et al, ). However, cell transmission often occurs in melanoma tumors initially classified histologically as a non‐metastatic primary tumor.…”
Section: Introductionmentioning
confidence: 99%